Faktor Risiko Kepatuhan Pengobatan pada Penderita Tb Paru BTA Positif - Rojali Rojali; Noviatuzzahrah Noviatuzzahrah (Jurnal Kesehatan, 2018)
This study was to determine the factors that affect the compliance of treatment of tuberculosis patients smear-positive pulmonary in Community Health Centers Cipondoh, Tangerang, Banten, the year 2015-2016. This research design was "case-control". The population was all positive pulmonary tuberculosis patients who received treatment and recorded in the listing sheet of TB-01 of Cipondoh Community Health Centers. Total samples were 35 people which been meet the inclusion and exclusion criteria. The result showed treatment compliance description which was 80% of tuberculosis pulmonary patients obedient to medication. A predisposing factor was 74.3% for men; 82.9% new types of sufferers; 82.9% duration of treatment 6 months. The enabling factor was 37.1% of the distance to the Community Health Centers 1.26 km. The reinforcing factor of 80% did not have supervisor taking medicine. Analysis of the correlation between predisposing factor and compliance of tuberculosis treatment of smear-positive pulmonary, there was no relationship for gender variable, patient type, duration of treatment, and distance of home to Community Health  Centers. Analysis of the correlation between reinforcing factor with compliance of tuberculosis treatment of smear-positive obtained no relation for the variable status of supervisor taking medicine.